2020
DOI: 10.1080/1828051x.2020.1745097
|View full text |Cite
|
Sign up to set email alerts
|

A commercial macroalgae extract in a plant-protein rich diet diminished saturated fatty acids of Oncorhynchus mykiss walbaum fillets

Abstract: Seaweeds are considered novel feed ingredients, nutraceutical compounds and source of pigments and proteins. They appear to possess bioactive properties, such as hypolipidemic, antioxidant and immune-stimulative actions; furthermore, their proteins are considered just as nutritious as terrestrial vegetables. In the present work, rainbow trout (Oncorhynchus mykiss Walbaum) was fed for 95 days with three diets: a fishmeal-based positive control diet (Cþ), a vegetable protein-based negative control diet (CÀ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…On the contrary, in this study, the count levels of n-3 fatty acids and lipid species such as PC 22:5e-20:3 were reduced by all experimental groups. Additionally, Bruni et al [ 45 ] reported a commercial macroalgae extract in a plant-protein-rich diet with diminished saturated fatty acids fed to trout fillets, which is consistent with our study, mainly with the reduction in myristic acid, FAHFA and phospholipids containing saturated fatty acids with from 4 to 18 carbons.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the contrary, in this study, the count levels of n-3 fatty acids and lipid species such as PC 22:5e-20:3 were reduced by all experimental groups. Additionally, Bruni et al [ 45 ] reported a commercial macroalgae extract in a plant-protein-rich diet with diminished saturated fatty acids fed to trout fillets, which is consistent with our study, mainly with the reduction in myristic acid, FAHFA and phospholipids containing saturated fatty acids with from 4 to 18 carbons.…”
Section: Resultssupporting
confidence: 93%
“…Because the fatty acid profile in the body of fish reflects the fatty acid profile of their diet, several reports indicate that macroalgae supplementation could increase the amount of n-3 in the muscle of carnivorous fish and could counteract the total reduction in n-3 in trout fillet, as a consequence of the dietary inclusion of vegetable oils, such as rapeseed oil [ 10 , 45 ]. For example, the dietary inclusion of 10% Ulva lactuca resulted in a significant increase in trout muscle Docosapentaenoic acid (22:5n-3; DPA) levels at the end of the feeding period [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fresh water and certain euryhaline fish species, such as salmonids, are able to synthesize PUFAs starting form shorter-chain precursors through the elongation and desaturation pathways [ 76 ]. While considering the estimated activity of Δ5 and Δ6 desaturases on n-3 and n-6 PUFAs ( Table 7 ), the values obtained in the present trial were lower than those proposed for rainbow trout by Bruni et al [ 77 ], underlying a reduced ability of carpione in converting shorter FAs precursors in longer n-3 PUFAs.…”
Section: Discussioncontrasting
confidence: 89%
“…1(a) and 1(b), respectively. In addition, this crystal has a monoclinic symmetry belonging to the space group 2 1 / , and punctual group 5 2ℎ , with lattice parameters = 35.260(11)˚ , = 4.9487(16)˚ , = 9.406(3)˚ , and volume = 1658.0˚ 3 . Its unit cell contains 4 molecules and = 4 organized periodically through dimers arranged as alternating monolayers of the carboxyl group and methyl radicals parallel to the plane (010), build-up by the hydrophilic part the carboxylic acid through hydrogen bonds [17].…”
Section: Computational Approachmentioning
confidence: 99%
“…Currently, fatty acids have attracted the attention of the scientific community. Due to their fundamental properties, it has potential application in the medicine, pharmaceuticals, cosmetics technology, foods, and fuel fields [1][2][3][4][5][6][7][8], which requires great efforts to synthesize and characterize fatty acid crystals through experimental techniques. In this context, from an experimental or theoretical point of view, there is a fundamental importance to obtain better potentialities and overall properties comprehension of such structure [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%